Comparison of Spinach Sex Chromosomes with Sugar Beet Autosomes Reveals Extensive Synteny and Low Recombination at the Male-Determining Locus. (25th August 2016) - Takahata, Satoshi; Yago, Takumi; Iwabuchi, Keisuke; Hirakawa, Hideki; Suzuki, Yutaka; Onodera, Yasuyuki
Abstract: Spinach ( Spinacia oleracea, 2 n = 12) and sugar beet ( Beta vulgaris, 2 n = 18) are important crop members of the family Chenopodiaceae s . s . Sugar beet has a basic chromosome number of 9 and a cosexual breeding system, as do most members of the Chenopodiaceae s . s. family. By contrast, spinach has a basic chromosome number of 6 and, although certain cultivars and genotypes produce monoecious plants, is considered to be a dioecious species. The loci determining male and monoecious sexual expression were mapped to different loci on the spinach sex chromosomes. In this study, a linkage map with 46 mapped protein-coding sequences was constructed for the spinach sex chromosomes. Comparison of the linkage map with a reference genome sequence of sugar beet revealed that the spinach sex chromosomes exhibited extensive synteny with sugar beet chromosomes 4 and 9. Tightly linked protein-coding genes linked to the male-determining locus in spinach corresponded to genes located in or around the putative pericentromeric and centromeric regions of sugar beet chromosomes 4 and 9, supporting the observation that recombination rates were low in the vicinity of the male-determining locus. The locus for monoecism was confined to a chromosomal segment corresponding to a region of approximately 1.7Mb on sugar beet chromosome 9, which may facilitate future positional cloning of the locus.